Caracterização neuroquímica das vias da dor em ensaio pré-clínico de periodontite - Lima, Joanna Trycia Magalhães Alexandre (2019)
Periodontitis (PE) is a chronic immunoinflammatory disease with dental loss, and despite extensive tissue destruction, there is no painful symptomatology, raising questions about which neuronal changes occur. This work focuses on the neurochemical characterization of pain pathways in a pre-clinical periodontitis test. PE was induced in Wistar rats by ligation of nylon wire around the left 2nd maxillary molars. Between days 0 to 21, a mechanical nociception analysis was performed (Von Frey). For behavioral analysis by the formalin test, on days 1, 3, 5, 7, 11, 14 and 21, rats received either formalin (0.5%) or saline (sc) injection. After nociceptive evaluation, the animals were perfused, euthanized and excised: the maxilla, gum (GU), trigeminal ganglion (TG) and caudal subnucleus (CS). The parameters evaluated were: alveolar bone loss analysis (ABL); quantification of the levels of proinflammatory mediators: TNF-α IL-1β, IL-8 and PGE2 in GU; quantification of neurotransmitter levels: SP, CGRP and GLu in GU, TG and CS; immunohistochemistry of the potential transient vanilloid receptor 1 (TRPV1) in TG; analysis of the gene expression of MOR (μ) and KOR (ƙ) opioid receptors in GU and TG; and analysis of the protein expression of μ and ƙ receptors in TG. In ABL, rats submitted to PE showed greater bone loss on days 7, 11, 14 and 21, compared to normal. There was a significant increase of TNF-α, IL-1β, IL-8 and PGE2 on the 11th day of PE in relation to the normal group. In the analysis of mechanical nociception, there was a reduction of the head withdrawal threshold on the 11th day of PE in relation to day 0 and 11 of the normal group. On the 17th day of PE, there was an increase in the threshold compared to the 11th day of PE. In formalin nociception, only the eleventh day of PE that received formalin showed a significant increase in the nociceptive behavior in relation to the normal (saline or formalin) and to the 11th day of PE that received saline. In the dosages of SP, GLu, CGRP and in the analysis of TRPV1 expression there were no statistical differences between the groups. In the analysis of the gene expression of the opioid receptors in GU, a significant increase of MOR was observed on days 7 and 11 of PE, and of KOR on day 7 of PE in relation to normal. In TG, gene expression and protein levels of MOR increased on the 11th and 14th days, and KOR increased on the 11th day of PE in relation to normal. It is suggested that PE evokes peripheral sensitization on day 11 mediated by TNF-α, IL-1β, IL-8 and PGE2, but does not increase TRPV1, nor does it alter the release of SP, CGRP and GLu. Concomitantly, endogenous pain inhibition by μ and ƙ opioid receptors occurs in primary afferent fibers and TG.